Penerapan Budaya Positif Parsel Si Margaret SD Negeri Wonorejo - Dewi Nuraeni (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Positive Culture is very important to implement in elementary schools, especially at Wonorejo State Elementary School. Through Positive Culture, good habits can grow optimally and consistently. For this reason, it is necessary to implement the Positive Culture "Parsel Si Margaret" consistently and sustainably.